Numerical investigation of CFRP strengthened full scale CFST columns subjected to vehicular impact. (1st November 2016) - Alam, Md Iftekharul; Fawzia, Sabrina; Zhao, Xiao-Ling
Highlights: Full scale bare and CFRP strengthened CFST columns are developed numerically. Dynamic impact simulation is performed using realistic vehicle model. CFRP wrapping provides enhanced impact resistance compared to ordinary CFST columns. The advantages of CFRP wrapping of CFST columns are investigated in parametric studies. Abstract: In recent years, the risk of damage or failure of axial load bearing structural members has increased rapidly due to increase of accidental vehicle/ship collision events. Therefore, suitable strengthening technique needs to be developed to minimise the casualty and economic loss caused by vehicular collisions with structural columns. In this study, numerical simulations are carried out to evaluate the effect of carbon fibre reinforced polymer (CFRP) strengthening of full scale concrete-filled steel tubular (CFST) columns under vehicular impact. Numerical models of bare and CFRP strengthened CFST columns were first developed and validated in a recent study of the authors. The validated finite element (FE) models are extended to full scale columns. Realistic vehicle behaviour is simulated with simplified mass-spring vehicle model. The outer diameter of steel section is kept same and the wall thicknesses are changed to account the slenderness effects of hollow steel sections. Both vehicle and column deformations are considered during the impact simulation as observed in practical situation. The dynamic impact analysis results show that adhesively bonded CFRP sheets provide enhanced impact resistance capacity of strengthened columns by reducing lateral displacement about 40% compared to ordinary CFST columns. A comprehensive parametric study is conducted by varying the vehicle velocity, vehicle mass, axial static loading, vehicle stiffness and CFRP bond length to observe the effects of these parameters on the structural responses of bare and wrapped columns. CFRP wrapping is found to be a promising strengthening technique to control global failure of full scale CFST columns subjected to vehicular impact.